Skin aging from mechanisms to interventions: focusing on dermal aging - Shin, Sun Hye; Lee, Yoon Hwan; Rho, Nark-Kyoung; Park, Kui Young (Frontiers in Physiology, 2023)
Skin aging is a multifaceted process that involves intrinsic and extrinsic mechanisms that lead to various structural and physiological changes in the skin. Intrinsic aging is associated with programmed aging and cellular senescence, which are caused by endogenous oxidative stress and cellular damage. Extrinsic aging is the result of environmental factors, such as ultraviolet (UV) radiation and pollution, and leads to the production of reactive oxygen species, ultimately causing DNA damage and cellular dysfunction. In aged skin, senescent cells accumulate and contribute to the degradation of the extracellular matrix, which further contributes to the aging process. To combat the symptoms of aging, various topical agents and clinical procedures such as chemical peels, injectables, and energy-based devices have been developed. These procedures address different symptoms of aging, but to devise an effective anti-aging treatment protocol, it is essential to thoroughly understand the mechanisms of skin aging. This review provides an overview of the mechanisms of skin aging and their significance in the development of anti-aging treatments.